The Effect of Price and Ease of Use on Customer Loyalty: A Case Study of Repeat Transaction Interest Through the OVO Application - Setyani Dwi Lestari; Selamet Riyadi; Sugeng Priyanto; Anie Suhermin (Golden Ratio of Marketing and Applied Psychology of Business, 2023)
The study aims to examine the effect of price, ease of use, loyalty of interest in re-transacting with OVO on customer loyalty which is tested both directly and indirectly. The population used amounted to 80 respondents. The results of this study state that 1). Price has a positive and significant effect on interest in re-transacting the OVO application. 2). Ease of use has a positive and significant effect on interest in re-transacting the OVO application. 3). Price has a positive and significant effect on customer loyalty for the OVO application. 4). Ease of use has a negative and significant effect on customer loyalty for the OVO application. 5). Price has a direct influence on customer loyalty, but on the contrary, it does not have a direct effect through the interest in re-transacting the OVO application. 6). Ease of use has a direct influence on customer loyalty but otherwise has no direct effect through interest in re-transacting the OVO application. 7). Interest in re-transactions has a positive and significant effect on customer loyalty for the OVO application.